Calibration of an Upconverting Phosphor-Based Quantitative Immunochromatographic Assay for Detecting Yersinia pestis, Brucella spp., and Bacillus anthracis Spores - Zhang, Pingping; Zhang, Yuanyuan; Zhao, Yong; Song, Yajun; Niu, Chunyan; Sui, Zhiwei; Wang, Jing; Yang, Ruifu; Wei, Dong (Frontiers in Cellular and Infection Microbiology, 2020)
Abstract: Y. pestis, Brucella spp., and B. anthracis are pathogens that can cause infectious zoonotic diseases with high mortality rates. An upconverting phosphor-based quantitative immunochromatographic (UPT-LF) assay, a point-of-care testing method, was calibrated to quantitatively detect pathogenic bacteria. The bacterial purity or activity were ensured via staining methods and growth curves, respectively. The assay showed that the classic plate-counting method underestimated the bacterial numbers compared with those of the bacterial counting method as per the reference material of the National Institutes for Food and Drug Control, China. The detection results of the UPT-LF assay differed significantly between the bacterial cultures in liquid and solid media and between different species strains. Accelerated stability assessments and freeze-thaw experiments showed that the stability of the corresponding antigens played an important role in calibrating the UPT-LF assay. In this study, a new calibration system was developed for quantitative immunochromatography for detecting pathogenic bacteria. The results demonstrated the necessity of calibration for standardizing point-of-care testing methods.